miR-34-5p mediates 20E-induced autophagy in the fat body of Bombyx mori by targeting Atg1 - Huili Qiao; Ziqian Tong; Yuanzhuo Wang; Juanjuan Yang; Yanyan Sun; Huixuan Shi; Zhuo Liu; Jianping Duan; Dandan Li; Yunchao Kan (BMC Genomics)
Abstract Background 20-Hydroxyecdysone (20E) is an important hormone that regulates insect development and metamorphosis. The fat body of insects plays a crucial role in nutrient storage and energy metabolism and is considered the exchange center for regulating insect development. The fat body undergoes remarkable transformation during insect metamorphosis and is primarily regulated by 20E. microRNAs (miRNAs) have been identified in different insects and have multiple functions in various physiological processes. However, the interaction of 20E and miRNAs in fat body regulation remains unclear. Results We constructed six small RNA libraries using Bombyx mori fat body treated with 20E. Expression and functional analyses were conducted to identify 20E-responsive miRNAs. In total, 431 miRNAs were identified, including 389 known and 42 novel miRNAs. Differential expression analysis revealed significant expression changes in the expression of 40, 9, and 18 miRNAs at 2 h, 6 h, and 12 h after 20E treatment, respectively. The expression of 10 miRNAs was validated using quantitative real-time PCR. miR-34-5p is a highly conserved miRNA among the 10 validated miRNAs, and autophagy-related gene 1 (Atg1) was considered a target gene of miR-34-5p. The expression analysis of miR-34-5p and Atg1 exhibited an opposite expression pattern in the fat body after the 20E treatment. Dual-luciferase assay indicated that miR-34-5p could inhibit Atg1 expression by targeting a binding site in CDS region of Atg1. In larval fat body, overexpressing miR-34-5p by injecting miR-34-5p agomir suppressed the expression of Atg1 and autophagy, whereas knocking down miR-34-5p by injecting miR-34-5p antagomir induced the expression of Atg1 and autophagy. Meanwhile, Atg1 silencing by RNAi also inhibited autophagy. These results indicate that miR-34-5p participates in 20E-induced autophagy in B. mori fat body by interacting with Atg1. Conclusions We systematically identified and functionally characterized miRNAs associated with 20E regulation in the fat body of B. mori. miR-34-5p is involved in 20E-induced autophagy in B. mori by regulating its target gene Atg1. These results provide insight into the role of sophisticated interactions between miRNAs, 20E regulation, and autophagy in fat body remodeling and insect metamorphosis.